KEBIJAKAN PENCEGAHAN TINDAK PIDANA PENCURIAN KENDARAAN DI AREA PARKIR KAMPUS: STUDI DI UNIVERSITAS SUMATERA UTARA - H. I. H, ferdinan; Mulyadi, Mahmud; Trisna, Wessy (Penerbit Lafadz Jaya, 2025)
The University of North Sumatra (USU) as an educational institution is not free from theft crimes, but until now it has not had a specific policy in preventing these crimes. In fact, a safe and comfortable campus environment is very important for the smooth running of the teaching and learning process. This study aims to analyze the regulation of theft crime prevention at USU and the urgency of forming special regulations related to theft prevention on campus. This study uses a juridical-empirical method with a legislative approach and field studies through interviews with USU academics. The data used include relevant laws and regulations and interview results, which are then analyzed normatively-qualitatively. The results of the study show that USU does not have a specific policy in preventing theft crimes, so preventive measures are needed from internal parties and cooperation with the police. In addition, the urgency of forming prevention regulations on campus is very high in order to accommodate prevention efforts through improving facilities and infrastructure, improving the quality of security human resources, and implementing uniform SOPs. This regulation is expected to strengthen campus security and reduce crime rates in the USU environment.